Axiomatic definition of quantity as a basis for teaching metrology in Mechanical Engineering; Journal of Physics: Conference Series; Vol. 772 : Metrology Across the Sciences: Wishful Thinking? - Muravyov (Murav’ev) S. V. Sergey Vasilyevich (2016, 2016)
Title screen